PENGARUH LINGKUNGAN KELUARGA DAN PENGALAMAN PRAKTIK KERJA INDUSTRI TERHADAP MINAT BERWIRAUSAHA SISWA SMK - Farida Fadlilah; Sri Wahyuni; Leny Noviani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objective of research were to find out the effect of family environment and industrial working practice experience towards entrepreneurship interest in XI grade. The method used in this study was descriptive quantitative method with survey . The sample in this study were 151 students XII grade in SMK Batik 1 Surakarta academic year 2015/2016. The data collection techniques used  questionnaires.  The  data  were  analyzed  by  using  multiple  regression analysis. The results showed that there was a significant positive effect of family environment and industrial working practice experience  simultaneously  towards  entrepreneurship interest. The magnitude of the effect of family environment and industrial working practice experience towards entrepreneurship interest simultaneously obtained from the calculation of the R- square of 41,5%.